Evaluation of the effect of biological elicitors on the resistance to salinity stress in the date palm (Phoenix dactylifera L., cv. Stameran) - Bita Sadeghi; Vahid Abdossi; Vahid Zarrinnia; Nader Hasanzadeh (Acta Scientiarum Polonorum: Hortorum Cultus, 2023)
An experiment was conducted in a completely randomized design (CRD) with factorial arrangement with three treatments of salinity (0 or check, 150, and 300 mM), and five bacterial elicitors treatments (fungal consortium (bioactive) (BFC), fungal elicitor at 1,000 ppm concentration (EL1), fungal elicitor at 2,000 ppm concentration (EL2), bacteria (BS) (Bacillus safensis), and bacteria (BP) (Bacillus pumilus)) in the Horticultural Science Laboratory to evaluate the effect of biological elicitors, including fungi and bacteria, on resistance to salinity stress in the date palms. The results showed that the lowest hydrogen peroxide content (278 µmol/g) was found in the elicitor of B. safensis at the zero salinity level. Catalase enzyme activity was higher in the treatments of fungal elicitor at 2,000 ppm concentration and the zero salinity level, B. safensis at the 150 mM salinity level, and fungal consortium at the 300 mM salinity level. The hydrogen peroxide content in the plant decreased as the activity of PAL and PPO enzymes increased. Applying an elicitor may reduce the effects of salinity stress in the date palm, but the stress level could determine the impact of each elicitor.